2013
DOI: 10.1111/cdep.12018
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Income Instability for Children's Well‐Being

Abstract: Income instability is an important and understudied dimension of the established empirical relation between family income and children's healthy development. Frequent fluctuations in income may influence daily processes and routines of family life, but the nature of such effects also may vary by specific patterns of income instability, parents' responses, and children's characteristics. In this article, we review existing theory and research on income, family functioning, and child development to better unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 35 publications
7
105
0
Order By: Relevance
“…The finding that children in the lowest income trajectory had a markedly increased risk for early adulthood psychiatric disorder confirms previous associations found between childhood economic disadvantage and psychiatric disorder,4 5 12 13 27 especially among children living in poverty 28 29. Families in this group had annual mean incomes below the European Union's (EU) definition of relative poverty as an income below 60% of the median 30.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The finding that children in the lowest income trajectory had a markedly increased risk for early adulthood psychiatric disorder confirms previous associations found between childhood economic disadvantage and psychiatric disorder,4 5 12 13 27 especially among children living in poverty 28 29. Families in this group had annual mean incomes below the European Union's (EU) definition of relative poverty as an income below 60% of the median 30.…”
Section: Discussionsupporting
confidence: 84%
“…Several mechanisms explaining these associations have been suggested 1 9 12 14 28. Family financial hardship is intertwined in a complex manner with several co-factors, such as parenting quality, family structure and parent psychological factors, all of which may affect children's mental health 28.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The longer the experiences of job loss lasted, worst results of youth development and welfare effects were found (Frasquilho, de Matos, Gaspar, & de Almeida, 2016). The same study illustrated that depending upon families income level and trend of that income overtime, income instability can have variable and detrimental consequences for children's well-being (Frasquilho, de Matos, Gaspar, & de Almeida, 2016;Hill, Gennetian, Wolf, & Tubbs, 2013). To slightly contradict this finding, research has also indicated an alternative pathway to relatively less damaging outcomes of young adult's livelihood during economic hardships.…”
Section: More Recent Researchmentioning
confidence: 92%